Factors Affecting the Process of Anodic Dissolution Under Electropolishing Conditions by Adsorption of Polymers Molecules on Carbon Steel Surface - El-Shamy, Hamdy F.M.; Aggour, Y.A.; Ahmed, A.M.; El-Batouti, Mervette (Asian Journal of Chemistry, 2017)
Many corrosion inhibitors can be used to eliminate the undesirable destructive effect and prevent carbon steel dissolution. Polymers were found to inhibit the process of anodic dissolution. It is found that the limiting current of anodic dissolution decreases with increasing concentration of the natural polymers (viz., starch, chitosan, cellulose acetate and carboxymethyl cellulose sodium salt) which indicated the increase in inhibition efficiency and the stabilization of passive layer of polymers molecules as protective film on carbon steel surface. The effect of viscosity of the solution at different concentrations and temperatures were studied. Dissolution rate and percentage inhibition was determined by weight loss method. Values of activation energy indicate that the rate controlled step is the diffusion of aqueous species in the boundary layer and the isokinetic temperatures were estimated. Those polymers verify Flory-Huggins isotherm. Negative values of free energy of adsorption revealing to the spontaneous adsorption of polymers molecules on carbon steel surface. The adsorption of these polymers molecules on the anode surface was confirmed by scanning electron microscopy. Forced convection mechanism were applied and we obtained that the flow in system were turbulent flow.